2002
DOI: 10.1021/jf020306k
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oils Improve Lipid Metabolism and Increase Antioxidant Potential in Rats Fed Diets Containing Cholesterol

Abstract: The effect of olive oils on lipid metabolism and antioxidant activity was investigated on 60 male Wistar rats adapted to cholesterol-free or 1% cholesterol diets. The rats were divided into six diet groups of 10. The control group (control) consumed the basal diet (BD) only, which contained wheat starch, casein, cellulose, and mineral and vitamin mixtures. To the BD were added 10 g/100 g virgin (virg group) or Lampante (Lamp group) oils, 1 g/100 g cholesterol (chol group), or both (chol/virg group) and (chol/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 39 publications
4
37
0
5
Order By: Relevance
“…36) The literature related to atherosclerosis has emphasized the beneficial effects of MUFA containing oils, especially olive oil, on lipids and lipid peroxidation. 3,[9][10][11][12][13][14] But the effects of HO consumption on serum lipids and lipid peroxides are not clearly known. In our study, an HO diet given alone to normal rabbits did not affect plasma or tissue lipids, or prooxidant-antioxidant status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36) The literature related to atherosclerosis has emphasized the beneficial effects of MUFA containing oils, especially olive oil, on lipids and lipid peroxidation. 3,[9][10][11][12][13][14] But the effects of HO consumption on serum lipids and lipid peroxides are not clearly known. In our study, an HO diet given alone to normal rabbits did not affect plasma or tissue lipids, or prooxidant-antioxidant status.…”
Section: Discussionmentioning
confidence: 99%
“…7,8) On the other hand, monounsaturated fatty acids (MUFAs), like PUFAs, have been reported to have antilipidemic effects. 3,9) Since MUFAs are resistant to oxidation, they may lower the susceptibility of the organism to lipid peroxidation [9][10][11][12] and LDL oxidation. 13,14) Olive oil, which is rich in MUFAs, and is known as an antiatherogenic oil, has been gaining importance in nutrition.…”
mentioning
confidence: 99%
“…In the rats of Chol/Virg and Chol/Lamp vs. Chol diet groups, the added oils significantly hindered the decrease in the plasma antioxidant activity (TRAP, 21.2 and 16.7 %; and MDA, 27.0 and 22.3 %, respectively). According to the used antioxidant assays (TRAP), virgin and to less degree other olive oils possess high antioxidant potential [113,114].…”
Section: Olive Oilsmentioning
confidence: 99%
“…Gimeno E. et al, 2010 [23] reported that daily consumption of virgin olive oil about 2 tablespoons for 1 week helps in the lowering of LDL cholesterol oxidation and increases the antioxidant compounds in the blood. It has also been reported that olive oil maintained the plasma lipid pool by regulating the lipid peroxidation and antioxidant parameters [24]. Several studies in vitro suggest that, lipoxygenases, platelet aggregation and eicosanoid production were inhibited by olive oil phenolic compounds [25] [26].…”
Section: Introductionmentioning
confidence: 99%